Pengaruh Teknik Pengolahan Makanan terhadap Kandungan Nutrisi dalam Masakan Tradisional Gudeg: Penelitian - Tri Wahyuni Indah Permata; Mohamad Fairuz Gustin Abdiel (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Gudeg is one of Yogyakarta's traditional dishes, renowned for its distinctive flavor and unique preparation process. This study aims to analyze the impact of cooking techniques on the nutritional content of traditional gudeg. Three cooking methods were compared: slow cooking, high-temperature short-duration boiling, and steaming. The results showed that slow cooking produced deep flavors and tender textures but significantly reduced water-soluble vitamins such as vitamin C. High-temperature short-duration boiling preserved more vitamins but resulted in a harder texture and less complex taste. Meanwhile, steaming was the best technique for preserving nutrients, especially vitamins, but the distinctive flavor of gudeg was less pronounced. This study provides insights for the culinary industry to optimize cooking techniques to balance nutritional value and sensory characteristics in traditional dishes.